Knowledge Management and Job Performance: The Case of Lebanese Banking Sector - El-Chaarani, Hani; El-Abiad, Zouhour (International Review of Management and Marketing, 2020)
This study examines the impact of knowledge management on the job performance of Lebanese banking sector during 2019. The research employed knowledge acquisition, knowledge sharing, knowledge creation, knowledge codification and knowledge retention as proxies to analyze the knowledge management variable. The job performance is measured by considering quantitative and qualitative variables. The research reveals that knowledge acquisition, knowledge sharing, knowledge creation and knowledge retention have a positive impact on the job performance of the Lebanese banking sector. The result also reveals a non significant impact of knowledge codification on the job performance. The knowledge management should be as a mandatory condition in banking sector for making high level of job performance. Keywords: Knowledge Management, Job Performance, Banking Sector, Technology, Knowledge Retention. JEL Classifications: M1, M12, D8 DOI: https://doi.org/10.32479/irmm.9245